Caries Risk Assessment in Children Suffering From Obesity in Lattakia City (Cross-sectional study) - ابو كرم, غدير; فائق أحمد بدر (Latakia University Journal -Medical Sciences Series, 2024)
Introduction: The World Health Organization has classified dental caries as a non-communicable disease that requires bacterial plaque to occur, in addition to the role of several various risk factors - biological, genetic, behavioral, social, economic, shared with other non-communicable diseases, for example diabetes and obesity. Obesity is one of the conditions that has increased significantly throughout the world, especially in children, and has caused public health concern. Study objectiv: Verify the existence of a correlation between obesity and caries risk in children. Materials and methods: A cross-sectional study that included 370 children from schools in Lattakia city, whose ages ranged between (8-9) years. Anthropometric measurements were taken and dental examination according to the DMFT\dmft index was conducted to evaluate the risk of caries. Results: It was found that the caries risk in obese children was statistically significantly lower than the caries risk in underweight children at a confidence level of 95%.(P<0.05) Conclusion: The risk of caries is higher in underweight children than obese children, which requires increasing care and dental awareness programs for this group of children.